Subversion of Heteronormativity in Jeanette Winterson’s Oranges Are Not the Only Fruit - Bhusal , Purna Chandra (SCHOLARS: Journal of Arts & Humanities, 2025)
This article argues that Oranges Are Not the Only Fruit, a novel by Jeanette Winterson, challenges conventional discourses of gender and sexuality through its portrayal of the protagonist Jeanette’s subversive queer performances. Drawing on queer theory and employing content and textual analysis, the article discusses how Winterson represents queer embodiment not only as a form of resistance to heteronormativity but also as a means of pursuing self liberation from heteronormative indoctrination. The article concludes that Winterson subverts the heteronormative discourses on gender and sexuality through four queer interventions: demystification of essentializing human identity and truth, dramatization of the resisting queer drives, articulation of the liberating potential of queer desires/bodies, and portrayal of the possibility of queer love. Hence, the article contributes a fresh perspective on the novel and encourages further scholarly engagement with queer narratives in literary criticism and the real social world.